Hypersensitivity reactions to biologics used in the treatment of allergic diseases: clinical features, diagnosis and management - Sitek, Andrea; Chiarella, Sergio E.; Pongdee, Thanai (Frontiers in Allergy, 2023)
Several monoclonal antibodies have been approved by the Food and Drug Administration (FDA) to treat allergic disorders, including omalizumab, dupilumab, mepolizumab, reslizumab, benralizumab, tralokinumab and tezepelumab, and their indications continue to expand. Although the risks associated with these agents are overall low, hypersensitivity reactions have been described and are reported more frequently with increased use. We provide a comprehensive review of clinical features, diagnosis and management of hypersensitivity reactions attributed to these agents. We aim to provide useful information for the clinician managing hypersensitivity reactions to these monoclonal antibodies, as well as highlight the need for future research to address specific gaps in knowledge.